Answer:
![21\text{ m/s}](https://img.qammunity.org/2023/formulas/mathematics/college/za52uv64wfw93vv88h2ctcf7x8icetzhxu.png)
Step-by-step explanation:
Here, we want to get the velocity of the particle when the acceleration is zero
From the question, we have to differentiate twice to get the acceleration:
Now, let us get the value of t wt which acceleration is zero:
![\begin{gathered} Given\text{ x\lparen t\rparen} \\ x^(\prime)^\left(t\right)\text{ = 3t}^2-12t\text{ +}9 \\ x^(\prime)^(\prime)\left(t\right)\text{ = 6t-12} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/yzpo86ep7jm1xjjkh14a9ftdxv0at52sgf.png)
Now, let us calculate the t value when the second differential is zero
Mathematically, we have that as:
![\begin{gathered} 6t-12\text{ = 0} \\ 6t\text{ = 12} \\ t\text{ = }(12)/(6) \\ t\text{ = 2 secs} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/32oldyhvzu4h4culd0vq4gz0pa3jdwfkml.png)
What this simply means is that the acceleration is zero when t = 2
Now, let us get the velocity when t = 2
We simply substitute the value of t into the first differential
Mathematically, we have that as:
![x^{^(\prime)\text{ }}\left(2\right)\text{ = 3\lparen2\rparen}^2-12\left(2\right)\text{ + 9 = 12-24 + 9 = 21 }](https://img.qammunity.org/2023/formulas/mathematics/college/u257p7smsiqteoi2a4qhno02k8a21vysud.png)